How Important is Vocational Public Relations Support in Establishing Partnerships with the Business World/Industrial World (DU/DI)? - Yuli Agustina; Rosalina Dhea Anisa Chintya Dewi; Andi Basuki (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study aimed to determine the public relations activities of vocational high schools (SMK) in connecting between schools and the community, one of which is DU/DI. The purpose of this study was to determine public relations activities at SMK, forms of partnership with DU/DI and forms of public relations activities in supporting partnerships with DU / DI at SMK. This type of research was qualitative research. Collecting data was from a natural setting by using the researcher as a key instrument. Sources of data in the study were the results of interviews, documents, and social environment. The form of vocational partnership with DU/DI consisted of 9 cooperation forms and forms of public relations activities in support of partnerships with DU/DI was to conduct industry visits regularly, renewed the form of cooperation with DU/DI, as well as being an intermediary between Internship students and DU/DI. Overall results illustrated that school public relations activities in collaboration with DU/DI had been going well, but it had not been maximized.